Human Milk Fortification in Very Preterm Infants in China: A Multicenter Survey - Lin, Rong; Shen, Wei; Wu, Fan; Mao, Jian; Liu, Ling; Chang, Yanmei; Zhang, Rong; Ye, Xiuzhen; Qiu, Yinping; Ma, Li; Cheng, Rui; Wu, Hui; et al. (Frontiers in Pediatrics, 2022)
Aim: To investigate the use of human milk fortifier (HMF) for very preterm infants (VPIs) and complications and nutritional status of VPIs due to various breast milk enhancement strategies among the Chinese population. Methods: VPIs with birth weight < 1800 g and wholly or predominantly breastfed were assigned to the following fortification groups: no HMF, early HMF (adding HMF at an enteral volume of ≤ 80 mL·kg-1·d-1), middle HMF (adding HMF at an enteral volume of 80-100 mL·kg-1·d-1), and late HMF (adding HMF at an enteral volume of ≥ 100 mL·kg-1·d-1). The growth status and complications for various groups were evaluated. Results: We enrolled 985 VPIs, of which 847 VPIs (86.0%) received HMF, whereas 138 VPIs (14.0%) did not. The number of VPIs in the early, middle, and late fortification groups were 89 (9.0%), 252 (25.6%), and 506 (51.4%), respectively. The complete fortification was achieved of the early, middle, and late fortification groups in 13.2 ± 11.0 days, 13.8 ± 11.7 days and 12.3 ± 13.0 days, respectively, without significant differences (P > 0.05). The groups did not exhibit significant differences in the incidence of feeding intolerance, necrotizing enterocolitis (Bell stage ≥ 2), late-onset sepsis, and metabolic bone diseases (P > 0.05). The middle fortification groups exhibited the fastest growth velocity and the least dramatic decrease in the Z-score of weight and length, and the lowest incidence of EUGR (35.7%); whereas the “no HMF” groups exhibited the slowest growth velocity and the largest decline in the Z-score, and the highest incidence of EUGR (61.6%). Conclusions: The usage rate of HMF was relatively low among Chinese VPIs, fortification often occurred in the late feeding stage, and the time to reach complete fortification was long. Adding HMF and different breast milk enhancement strategies did not increase the incidence of feeding intolerance and necrotizing enterocolitis. The enteral volume of 80-100 mL·kg-1·d-1 with HMF addition led to increased growth in the weight and length and lower EUGR incidence, indicating that the addition of HMF at the specific feeding volume might be the best practice for promoting growth.